Potensi Mie yang Diperkaya dengan Kelor, Ikan Gabus, Okra, dan Singkong Modifikasi sebagai Pencegah Stunting: The Potential of Noodles Enriched with Moringa, Snakehead Fish, Okra, and Modified Cassava for Stunting Prevention - Juliana Christyaningsih; Nur Hatijah; Laili Rahmawati (Universitas Airlangga, 2026)
Background: Pregnant women with chronic energy deficiency are at higher risk of delivering low birth weight and premature babies, increasing the likelihood of stunting by 1.66 times compared to those with normal nutritional status mothers. Therefore, nutrient-rich foods are essential to prevent stunting. Objectives: This study aims to analyze the nutritional content and sensory quality of noodles enriched with moringa leaves, snakehead fish, okra, and modified cassava. Methods: A laboratory experiment was conducted to determine the nutrient composition of each ingredient, and sensory evaluation was carried out by 25 semi-trained panelists from the Nutrition Study Program, Surabaya Health Polytechnic, Ministry of Health, Indonesia, using a 1–5 rating scale for aroma, color, taste, and texture. Results: The results showed that the highest protein content was found in snakehead fish flour (58.7%), fat in okra flour (21.48%), carbohydrates in modified cassava flour (88%), iron in moringa leaf flour (202 ppm), calcium in snakehead fish flour (3%), potassium in moringa leaf flour (0.84%), and sodium in snakehead fish flour (0.1%). The best sensory results were achieved with a noodle formulation of 83% wheat flour, 10% modified cassava flour, 2% okra flour, 2% moringa flour, and 3% snakehead fish flour. Conclusions: These enriched noodles demonstrated high nutritional value and good sensory acceptance.